2011
DOI: 10.2298/psi1101023t
|View full text |Cite
|
Sign up to set email alerts
|

The anisotropy of perceived distance: The eyes story

Abstract: The aim of this study is to determine whether the eye position shift changes perceived distance, that is, whether kinesthetic information from eye muscles affects distance perception. Two experiments were done, in a dark room (reduced-cue situation), with 27 participants, psychology undergraduates. Participants had a task to match distances of three stimuli, on three viewing directions, 0, 30 and 60 deg rees relative to the body. Head and body of participants were fixed, and they changed viewing directio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…Based on this, we can conclude that even if barriers increased path length, effects in path preference were not due to the path length, but clearly due to the required effort on a certain path. As mentioned before, effects of effort shown in this study can be related to other findings which indicate, for example, importance of effort for perceived distance in humans (Tošković, 2009(Tošković, , 2011(Tošković, , 2012Witt & Proffitt, 2008;Paterson et al, 2019). It seems like effort required to perform certain actions can be linked to perception of certain characteristics, such as distance.…”
Section: Situation 4 (All Factors Equalized)supporting
confidence: 81%
See 2 more Smart Citations
“…Based on this, we can conclude that even if barriers increased path length, effects in path preference were not due to the path length, but clearly due to the required effort on a certain path. As mentioned before, effects of effort shown in this study can be related to other findings which indicate, for example, importance of effort for perceived distance in humans (Tošković, 2009(Tošković, , 2011(Tošković, , 2012Witt & Proffitt, 2008;Paterson et al, 2019). It seems like effort required to perform certain actions can be linked to perception of certain characteristics, such as distance.…”
Section: Situation 4 (All Factors Equalized)supporting
confidence: 81%
“…It is previously reported that effort has an effect on animals' behavior (Salamone, 2009), and that rats tend to choose a smaller prize if it goes with less effort (Zhang et al, 2018). Also, in human subjects, it is reported that the effort needed to perform an action, can have a significant impact on perceived distance (Tošković, 2009(Tošković, , 2011(Tošković, , 2012. On that line, there is a possibility that walking on the mud required much more effort from the rats than walking on the wooden lining.…”
Section: Insert Figure 1 Herementioning
confidence: 99%
See 1 more Smart Citation